Selected Aspects of Ensuring the Accessibility of Historical Buildings for People with Mobility Impairments - Rymsza, Barbara; Kaperczak, Krzysztof (Protection of Cultural Heritage, 2022)
This chapter is devoted to the problem of providing people with mobility impairments, using wheelchairs or crutches, and the elderly, with access to monumental buildings located in historic public spaces in Poland. Authors present current technical- and construction-related regulations concerning passageway infrastructure and the needs that result from limitations faced by people with mobility impairments. Proposals for solutions to improve accessibility are also presented in visual form, making it easier to understand the proposed solutions and showing examples of ones already applied. The paper addresses the problem of adapting sidewalks, parking spaces and entrances to buildings to speciﬁc needs, while following recommendations on conservation issues arising from the protection of cultural heritage and the historical nature of spaces around monuments. Authors of this chapter have long worked on the subject of public spaces’ accessibility to people with disabilities, basing on their own experience of wheelchair use. This chapter aims to show historic site administrators how accessibility to historic sites can be improved with minimal intervention and how cultural assets can be made enjoyable to people with special needs.